Faktor-Faktor Penentu Lokasi Sentra Industri Gula Kelapa (Studi Kasus: Di Wilayah Kecamatan Nglegok, Kabupaten Blitar) - Sudarsono, Fauzi Guspradana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Agro-industry sector is the economic driver of the villagers, the role of the manufacturing sector on the economy of the developing village. Coconut sugar industry is the manufacturing sector agroindustrial processing results to be obtained palm sap. Processing of coconut sugar will be more efficient if spatially concentrated in one location, it will lead to the growth of an industrial district in agglomeration in a region. Industrial centers of the region will be growing when considering the variables contained in the region to support the development of the industry to be efficient. The analysis of this study will be the variables contained in the industrial centers in the District Nglegok coconut sugar which is found as many as 13 varieabel. These variables were analyzed using factor analysis to obtain the results of the variable reduction. Of variables that will be obtained by the reduced per-variable to see which variables determine the location of industrial centers. The last phase is formed consisting of variable factors that shape. The results showed that there are 11 variables and 4 factors is formed. The most decisive factor is the efficiency factor supported spatial concentration factor and external factor while performance is not a determining factor Â Keywords :agglomeration,coconut sugar industry,factor analysis, location of industrial centers